Social Media as an Appliance to Pancasila Education for the Young Generation - Juliana Tirza; Wiputra Cendana (Jurnal Minfo Polgan, 2023)
Social media is not just a product of technology to satisfy human existence or a medium for human relations. Social media can be a medium of learning and self-potential development. The fact is that there are still many young people today who are mistaken in using social media. This paper tries to present survey data related to the use of social media as a medium for education about Pancasila and the practice of Pancasila values for the younger generation. The purpose of this paper is to find out how the use of social media can improve the practice of Pancasila values in everyday life. The method that has been used in this research is survey to a group of people between 18-28 years old. The data has been analyzed using descriptive analysis and explained in result and discussion. From the survey results, social media can be used as a means of Pancasila education for the younger generation, because social media chooses interestingly presented content to appear in the algorithm. Social media provides a discussion platform, filters and sharing are available to share knowledge with each other. It can be concluded that social media is very possible to be used and effective for Pancasila Education.